Metagenomic insights into genetic factors driving bacterial niche differentiation between bulk and rhizosphere soils - Wu, Xingjie; Bei, Shuikuan; Zhou, Xi; Luo, Yu; He, Zhibin; Song, Chunxu; Yuan, Huimin; Pivato, Barbara; Liesack, Werner; Peng, Jingjing (The Science of the total environment, 2023)
Cellular motility is crucial for effective colonization of the rhizosphere, but it is not yet clear whether bacterial motility is particularly linked to other genetic traits. Here, we applied genome-resolved metagenomics and phylogenomics to investigate the ecological significance of cellular motility for niche differentiation and the links between the genetic makeup of motile bacteria and rhizosphere colonization within a four-decade maize field experiment. Indeed, highly diverse sets of genes encoding cellular motility, including chemotaxis, flagellar assembly and motility proteins, and utilization of polymeric carbon were the important predictors of bacterial niche differentiation between bulk and rhizosphere soils. This is well exemplified by metagenome-assembled genomes encoding high motility capacity (hmc_MAGs). Their collective abundance was, on average, sixfold higher in rhizosphere soil than in bulk soil. All bulk-soil-derived MAGs showed low motility capacities (lmc). The hmc_MAGs were highly enriched in beneficial traits involved in carbohydrate utilization, assimilatory (nasA) and dissimilatory (nirBD) nitrate reduction, inorganic phosphate solubilization (gcd), and organic phosphate mineralization (phoD). Belonging to the families Sphingomonadaceae, Burkholderiaceae and Steroidobacteraceae, the hmc_MAGs showed a ninefold greater enrichment in these traits than proteobacterial lmc_MAGs and a twofold greater enrichment than 264 genomes publicly available for the above three families, thereby substantiating that a specific rhizosphere effect acted on the microbes represented by the hmc_MAGs. The particular link between the genetic capacities for high cellular motility and increased carbohydrate depolymerization as the key determinant for plant-selected rhizosphere colonization was further substantiated by the analysis of public bulk-rhizosphere soil metagenomes retrieved from wheat and cucumber field sites. [Display omitted] •Motility and polymer utilization capacity were highly enriched in rhizosphere.•Motility was significantly correlated with the utilization of polymeric carbon.•These two genetic traits act as the key determinants for niche differentiation.•Motility-encoding rhizosphere MAGs were enriched in beneficial genetic traits.•Potential contribution of these MAGs to maize yield